Effect of nutrition and endoparasitic treatment on growth, onset of puberty and reproductive activity in Menz ewe lambs - Mukasa-Mugerwa, E.; Kasali, O.B.; Said, A.N. (Elsevier, 1991)
Examines the effect of four levels of nutrition (poor, low, medium, and high) with or without endoparasitic treatment (drenching) on postweaning growth, survival and onset of puberty in Menz ewe lambs. A concentrate mixture providing 2.5 Mcal/kg dry matter (DM) metabolizable energy and 15.2 g/kg DM digestible protein was used. Assesses weaning weight, post-weaning daily gain and pubertal age and weight, post-weaning daily gain and pubertal age and weight of Menz ewe lambs. The results indicate that improved growth rate and body weight, resulting from better postweaning nutrition, affects the attainment of puberty.